Music therapy in context: Music, meaning and relationship - Pavlicevic, Mercedes (London Jessica Kingsley Publishers, 1997)
Addressing current music therapy debates to do with meaning, this text asks such questions as: are words necessary in creative music therapy?; how is clinical improvization distinct from "pure" music improvization, and if so what is the distinction?; and how do music therapists address culture-specific nuances in music, and in concepts of healing rituals? The text is divided into three sections. The first section explores concepts and theories developed by music theorists an dmusic psychologists in order to explore meaning in music as artform. The second section looks at the relationship between music and human emotion, in order to establish why, and on what basis, music is used as a therapeutic agent. Finally, the third section draws concepts from psychotherapy and music theory into the music therapy sphere. Music therapists are encouraged not to compromise the musical process at the heart of their practice, not simply to "borrow" concepts from allied theories, but to use these with authority.Show More Show Less